MEASUREMENT OF ETA'-SPIN PARITY - Cerrada, M; Wagner, F; Chaloupka, V; Hemingway, R; Holmgren, S; Losty, M; Loverre, P; Marzano, F; Blokzijl, R; Jongejans, B; Massaro, G; Schotanus, D; et al. (1977)
The spin parity of the η′ (958) is studied in the reaction K-p → η'Λ at 4.2 GeV/c, using bubble chamber data with a statistical sensitivity of 128 events/μb. The data unambiguously prefer the 0- assignment. © 1977.